The impact of the theft corner on the crime of theft on the classification of money crimes in Iraqi law - المدرس الدكتور محمد صباح سعيد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The crime of theft is a serious attack on property rights, and this attack occurs only if the offender takes possession of the money, and the legislator used the term "embezzlement" to express this attack. However, the element was not known, Criminal theory on two theories, traditional theory and modern theory (the theory ofThe theory of Garsonism - theory of possession), with adopting these theories are different concepts of the meaning of the corner of embezzlement, and these theories have had an impact on the classification of money crimes in penal legislation, according to the position taken by the legislator determines the classification of money crimes. From this aspect, this research dealt with the problematic aspects of the meaning of this element in the crime of theft. The meaning of this element was explained according to the traditional theory and its significance according to the modern theory (the theory of the theory of Garsonism theory of possession). The results of each theory and effect of these results Tabulation of money crimes. Finally, the position taken by the Iraqi legislator from these two theories, as well as the position of the Iraqi judiciary, was dealt with. During this research, the researcher proved that the Iraqi legislator had adopted the traditional theory and that the classification of money crimes in the Penal Code was based on this theory.